Burnout in palliative care physicians: a rapid review - Neethu Susan Abraham; Balbir Kumar; Sushma Bhatnagar (Palliative Medicine in Practice)
Burnout has nowadays become increasingly common in the medical field, especially among palliative care physicians. Burnout is characterized by emotional exhaustion, depersonalization, and a feeling of decreased accomplishment caused by occupation. Burnout in the previous times was ignored or not recognized much. Due to the demanding nature of the profession and long-term implications, the maintenance of self-care and prevention of burnout and compassion fatigue are important among palliative care physicians. This article stresses the importance of recognizing burnout and framing the strategies for preventing and dealing with it. It comprehensively analyses the gravity of the problem, the risk factors, signs, and symptoms, how to measure it, and its consequences, and also throws light on various management strategies.